IBM Rational ClearCase, Ant, and CruiseControl : the Java developer's guide to accelerating and automating the build process - Lee, Kevin A. (IBM Press, 2006)
Optimize your entire Java build and release process with ClearCase ® , Ant, and CruiseControl Better builds mean better software . Effective, regular build processes accelerate development and improve quality, helping you identify small problems early, before they grow complex and costly to fix. Now, there's a step-by-step guide to creating Java build processes that are right for your organization. Leading build and release management expert Kevin Lee introduces best practices for integrating and using three exceptionally powerful and recognized industry standard tools: IBM Rational® ClearCase software configuration management system, the open source Ant build tool, and CruiseControl for automating continuous builds. No previous build experience is necessary: Lee thoroughly explains everything from configuring SCM environments and defining build scripts through to release packaging and deployment. He offers solutions and techniques for both Base ClearCase and Unified Change Management (UCM)-IBM Rational's best practice Software Configuration Management usage model. Key techniques are presented in real-world context, through a full-fledged three-tier application case study. Whether you are a software developer, manager, or integrator, this book will help you create better builds-and reap the benefits in efficiency, traceability, quality, and speed. Coverage includes · Ensuring that every build you create is complete, consistent, and reproducible · Configuring a ClearCase-controlled environment to support your development organization's build and release process · Installing Ant and configuring it to build all of your project assets · Integrating Ant with ClearCase and effectively using them together · Installing CruiseControl and configuring it to schedule and automate different types of builds · Integrating CruiseControl with ClearCase to schedule builds and automate baselines and reports · Creating custom baseline and change request reports · Setting up automatic notification whenever build problems arise · Creating and packaging releasable, traceable builds with ClearCase and ClearQuestu2122